2019
DOI: 10.1017/wet.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Sugarbeet tolerance when dimethenamid-P follows soil-applied ethofumesate and S-metolachlor

Abstract: Sugarbeet growers only recently have combined ethofumesate, S-metolachlor, and dimethenamid-P in a weed control system for waterhemp control. Sugarbeet plant density, visible stature reduction, root yield, percent sucrose content, and recoverable sucrose were measured in field experiments at five environments between 2014 and 2016. Sugarbeet stand density and stature reduction occurred in some but not all environments. Stand density was reduced with PRE application of S-metolachlor at 1.60 kg ai ha–1 and S-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Although sugarbeet stature was affected by ethofumesate rate, ethofumesate did not reduce root yield in field experiments. These results were consistent with observations from other researchers (Bollman and Sprague 2007; Peters et al 2019; Smith and Schweizer 1983). Smith and Schweizer (1983) reported sugarbeet overcame early season injury from PRE and POST herbicides and did not affect yield.…”
Section: Resultssupporting
confidence: 94%
“…Although sugarbeet stature was affected by ethofumesate rate, ethofumesate did not reduce root yield in field experiments. These results were consistent with observations from other researchers (Bollman and Sprague 2007; Peters et al 2019; Smith and Schweizer 1983). Smith and Schweizer (1983) reported sugarbeet overcame early season injury from PRE and POST herbicides and did not affect yield.…”
Section: Resultssupporting
confidence: 94%
“…In contrast, sugarbeet density was greater in soils with OM > 3.5%, in field experiments or in greenhouse pots with Fargo silty clay (7.7% OM) or Bearden/Lindaas silt loam (4.7% OM) soils, because S-metolachlor was bound and not available in the soil solution (Pusino et al 1992;Shaner et al 2006). Other researchers have noted similar sugarbeet stand inconsistency following S-metolachlor application Dexter and Luecke 2004;Peters et al 2019). Previous research conducted by Peters et al (2019) reported sugarbeet density reduction occurred in some, but not all environments following S-metolachlor PRE at 1.60 kg ha -1 or S-metolachlor PRE at 0.80 kg ha -1 plus ethofumesate at 1.68 kg ai ha -1 alone or followed by POST applications of dimethenamid-P at 0.95 kg ha -1 .…”
Section: Rainfall Om Soil Series and S-metolachlor Ratementioning
confidence: 84%
“…Other researchers have noted similar sugarbeet stand inconsistency following S-metolachlor application Dexter and Luecke 2004;Peters et al 2019). Previous research conducted by Peters et al (2019) reported sugarbeet density reduction occurred in some, but not all environments following S-metolachlor PRE at 1.60 kg ha -1 or S-metolachlor PRE at 0.80 kg ha -1 plus ethofumesate at 1.68 kg ai ha -1 alone or followed by POST applications of dimethenamid-P at 0.95 kg ha -1 . Sugarbeet injury was greatest in environments with less than 3.5% OM (2.6% OM actual), when air temperature was cooler than in environments with no injury, and when cumulative rainfall to 14 d after seeding equaled or was greater than 40 mm (58 mm actual).…”
Section: Rainfall Om Soil Series and S-metolachlor Ratementioning
confidence: 84%
See 1 more Smart Citation
“…S-metolachlor reduced strawberry yield at 0.21 kg ha -1 , but only in selected, tested strawberry varieties (Boyd and Reed 2016). S-metolachlor at 2.16 to 4.32 kg ha -1 negatively affected sugar beet stand and growth while not influencing yield (Peters et al 2019). Sugar beet tolerance to S-metolachlor is variety-dependent (Bollman and Sprague 2008) and is reduced in soils with low clay and organic matter content (Lueck et al 2020).…”
Section: Italian Ryegrass Controlmentioning
confidence: 92%